Who Needs Direct-Acting Antivirals for HCV? Challenges Faced in Advancing HCV Therapy for HIV–HCV-Coinfected Individuals. Issue 5 (July 2013) - Klein, Marina B; Rollet, Kathleen C; Hull, Mark; Cooper, Curtis; Walmsley, Sharon; Conway, Brian; Pick, Neora; ,
Background: The recent availability of new direct-acting antivirals (DAAs) for HCV treatment, which significantly increase sustained virological response rates for genotype 1 HCV infection, has brought new optimism with respect to curative HCV treatment for HIV–HCV-coinfected patients. We describe the characteristics of coinfected patients who could be eligible for DAAs to determine potential challenges facing clinicians and patients hoping to take advantage of these new therapies. Methods: We evaluated the sociodemographic and clinical characteristics of the genotype 1 HCV–HIV-infected participants in a Canadian prospective multicentre cohort study at their most recent visit to assess potential eligibility for combination HCV treatment with boceprevir or telaprevir. Results: Of the 1, 020 coinfected participants enrolled in the cohort, 707 (85%) had evidence of chronic HCV infection (HCV-RNA-positive), of whom 497 (70%) were infected with genotype 1; 375 (75%) were naive to HCV treatment and 122 (25%) had previously received therapy and failed. Only 143 (38%) of HCV treatment-naive and 39 (32%) of treatment-experienced participants had no absolute contraindications for treatment. Alcohol abuse, active depression and decompensated liver disease were the most frequent reasons for treatment ineligibility. The majority would require alterations in antiretroviral regimens to avoid important drug–drug interactions. Conclusions: Although the need for curative HCV therapy in HIV–HCV coinfection is great, the actual number of patients who could be eligible for DAAs at the present time may be quite low. There remains an urgent need to develop safe, simple and interferon-sparing treatments for coinfected individuals.